Comparison of Postoperative Analgesic Effectiveness of Bupivacaine and Bupivacaine Plus Dexmedetomidine Wound Infiltration in Abdominal Surgeries under General Anesthesia: Comparison of Bupivacaine and Bupivacaine Plus Dexmedetomidine - Tariq, Hafsa; Shahid, Muhammad; Mohsin, Muhammad Usman; Shakeel, Naima; Afzal, Muhammad Shahzad; Rafique, Shahid (Pakistan Journal of Health Sciences, 2024)
Abdominal surgeries were major surgical procedures that were performed at any teaching hospital. Pain control was a major concern during intra-operative as well as post-operative periods in these patients. Objective: To compare post-operative analgesic effectiveness of bupivacaine and bupivacaine plus dexmedetomidine wound infiltration in abdominal surgeries under General Anesthesia. Methods: This randomized controlled trial was conducted at the Department of Anesthesia, Sahiwal Teaching Hospital Sahiwal from 1st April, 2024 till 31st May 2024. Sixty-four patients underwent a pre-operative assessment on the day before surgery. Both Groups received wound infiltration with studied drugs at the end of surgery. After surgery, patients were assessed for pain using a Visual Analog Scale (VAS) and data was collected and analyzed using Statistical Package for the Social Sciences (SPSS) version 26.0. Results: The mean post-operative analgesia duration of the patients on bupivacaine was 11.78 ± 1.64 but the mean post-operative analgesia duration of the patient on bupivacaine plus dexmedetomidine was 19.19 ± 2.49. (2-tailed significance 0.001). The mean opioid consumption in mg of the patients in bupivacaine was 20.69 ± 4.31 but the mean opioid consumption in mg of the patient in bupivacaine plus dexmedetomidine was 10.88 ± 4.53. (2-tailed significance 0.001). In bupivacaine, patients with bradycardia were 0% and patients without bradycardia were 100% but in bupivacaine plus dexmedetomidine, patients with bradycardia were 15.6% and patients without bradycardia were 84.4%. Conclusions: There was a difference in the analgesic effectiveness of dexmedetomidine when added to bupivacaine in wound infiltration in abdominal surgeries.